STRUCTURE FORMATION IN AQUEOUS SUSPENSION OF CELLULOSE (Proceedings of the YSU B: Chemical and Biological Sciences, 2012)
The formation of porous materials from the link of sulfates groups on the surface of cellulose whiskers by Ca2+ and Ba2+ cations has been studied. It has been shown that the introduction of this cations in suspension increases the viscosity of the system.
Keywords: cellulose; viscosity of the system; formation